Yield and Production Components of Corn Under Straw of Marandu Palisade Grass Inoculated With Azospirillum brasilense in the Low-Land Cerrado - Modesto, Viviane Cristina; Andreotti, Marcelo; Nakao, Allan Hisashi; Soares, Deyvison de Asevedo; Froio, Leonardo de Lima; Dickmann, Lourdes; Pascoaloto, Isabô Melina; Fernandes, Isabela Maria Dias Moyses (Frontiers in Sustainable Food Systems, 2021)
The use of plant growth-promoting bacteria combined with Integrated Agricultural Production Systems (IAPS's) has resulted in productivity increases in the Brazilian Cerrado region. Thus, the objective was to evaluate the effect of inoculating or not Azospirillum brasilense on corn and palisade grass seeds (Urochloa brizantha cv. Marandu) on growth, yield components, and dry matter yield of the aerial part and grains in an Oxisol cropped in ICLS and under no-tillage system for 12 years in an irrigated area. The experimental design was a randomized block design with four replications. The treatments were composed of Corn (monoculture) with inoculated seed; corn (monoculture) without inoculated seed; corn + palisade grass (intercropping) without inoculation; corn + palisade grass (intercropping) with inoculation in both seeds; corn + palisade grass (intercropping) with inoculation of corn seeds and corn + palisade grass (intercropping) with inoculation of grass seeds. At the end of each production cycle, the yield and components of corn, corn straw biomass, and dry-matter of palisade grass were evaluated. The optimal conditions of soil provided by liming and fertilization at sowing and nitrogen applied in topdressing, the application of A. brasilense in corn seeds did not express your potential. Intercropped systems inoculated or not with Azospirillum brasilense on corn seeds increases grain yield, dry matter production of grass, and nutrient accumulation in the straw, providing greater sustainability to the Cerrado no-tillage system.